2014
DOI: 10.1016/j.ypmed.2014.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Does active commuting improve psychological wellbeing? Longitudinal evidence from eighteen waves of the British Household Panel Survey

Abstract: ObjectiveThe aim of this study is to explore the relationship between active travel and psychological wellbeing.MethodThis study used data on 17,985 adult commuters in eighteen waves of the British Household Panel Survey (1991/2–2008/9). Fixed effects regression models were used to investigate how (i.) travel mode choice, (ii.) commuting time, and (iii.) switching to active travel impacted on overall psychological wellbeing and how (iv.) travel mode choice impacted on specific psychological symptoms included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
170
5
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(192 citation statements)
references
References 62 publications
12
170
5
5
Order By: Relevance
“…This CT-SWB association is mediated not only by experiences of traffic congestion but also reduced time for physically active leisure. For example, Martin et al (2014) use BHPS data to show that commute time spent walking slightly increases psychological well-being, whereas time spent driving decreases it.…”
Section: Prior Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…This CT-SWB association is mediated not only by experiences of traffic congestion but also reduced time for physically active leisure. For example, Martin et al (2014) use BHPS data to show that commute time spent walking slightly increases psychological well-being, whereas time spent driving decreases it.…”
Section: Prior Literaturementioning
confidence: 99%
“…Even the few studies that do investigate commute time's impact on subjective well-being (SWB), albeit mainly in Western settings, are inconclusive (Dickerson et al, 2014;Humphreys et al, 2013;Martin et al, 2014;Olsson et al, 2013;Roberts et al, 2011;Stutzer and Frey, 2008;Turcotte, 2011). These results are also difficult to generalize, especially to developing settings like China, where the increasing urban sprawl and traffic congestion in cities are particularly pronounced (Wang and Chai, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Wellbeing can be viewed as an indirect consequence of a number of opportunities that involve using shared space for different purposes, such as active commuting [39][40][41][42]; sharing work to increase economic wellbeing [43]; and sharing experiences to increase or improve social interactions.) Here, a range of spaces and artefacts are shared across and between residents, including rooftop allotment gardens, car club membership, and a café.…”
Section: Wellbeingmentioning
confidence: 99%
“…Furthermore, active commuting is associated with high levels of physical wellbeing (Humphreys et al, 2013). In addition, the relationship between active travel and psychological wellbeing has also been examined by Martin et al (2014), by providing important information about the positive impact on the overall psychological wellbeing by switching to an active travel mode. This study showed that there is a strong relationship between overall psychological wellbeing and active travel as well as public transport when compared to car travel, time spent for walking and driving, and switching from car travel to active travel.…”
Section: Benefits Of Physical Activitymentioning
confidence: 99%